Polymeric Nanocarriers with Luminescent Colloidal Nanoplatelets as Hydrophilic and Non-Toxic Two-Photon Bioimaging Agents - Nawrot KC (Dove Medical Press, 2021)
Katarzyna Celina Nawrot,1 Jan Kazimierz Zareba,1 Monika Toporkiewicz,2 Grzegorz Chodaczek,2 Dominika Wawrzynczyk,1 Julita Kulbacka,3 Urszula Bazylinska,4 Marcin Nyk1 1Advanced Materials Engineering and Modelling Group, Faculty of Chemistry, Wroclaw University of Science and Technology, Wroclaw, 50-370, Poland; 2Łukasiewicz Research Network - PORT Polish Center for Technology Development, Wroclaw, 54-066, Poland; 3Department of Molecular and Cellular Biology, Faculty of Pharmacy, Wroclaw Medical University, Wroclaw, 50-556, Poland; 4Department of Physical and Quantum Chemistry, Faculty of Chemistry, Wroclaw University of Science and Technology, Wroclaw, 50-370, PolandCorrespondence: Urszula BazylinskaDepartment of Physical and Quantum Chemistry, Faculty of Chemistry, Wroclaw University of Science and Technology, Wybrzeze Wyspianskiego 27, Wroclaw, 50-370, PolandTel +48 713202183Email urszula.bazylinska@pwr.edu.plMarcin NykAdvanced Materials Engineering and Modelling Group, Faculty of Chemistry, Wroclaw University of Science and Technology, Wroclaw, 50-370, PolandTel +48 713202316Email marcin.nyk@pwr.edu.plIntroduction: Semiconductor nanoplatelets (NPLs) are promising materials for nonlinear optical microscopy since they feature good two-photon absorption (TPA) properties, narrow photoluminescence spectra and high quantum yields of luminescence. Nevertheless, the use of semiconductor NPLs is inevitably connected with concerns about heavy metal ion toxicity and their intrinsically hydrophobic character.Methods: Our contribution focuses on the design and engineering of coloidal bionanomaterial consisting of two-dimensional highly luminescent CdSe semiconductor NPLs loaded into spherical and homogeneous polymeric nanocarriers (NCs) based on poly(ethylene oxide) and poly(propylene oxide) block co-polymer. The biocompatibility and usefulness of the NPLs-loaded polymeric NCs in two-photon induced bioimaging was demonstrated invitroby cytotoxicity and two-photon microscopic studies using eukaryotic (normal fibroblasts and cancer ovarian) cells.Results: The encapsulated NPLs maintain their intensive and spectrally narrow photoluminescence, as well as preserve good TPA properties, while the surrounding polymer shell imparts hydrophilic character and non-toxicity towards eukaryotic cells. Specifically, TPA cross-sections of the colloidal NCs loaded with NPLs show large values reaching up to 2.0 × 108 GM, with simultaneously two-photon brightness reaching 2.2 × 107 GM at 870 nm. MTT proliferation assay performed on cell lines treated with encapsulated NPLs revealed at least 70% viability of normal human gingival fibroblast (HGF) and cancer ovarian (MDAH-2774) cells, while the results of multiphoton imaging of murine (L-929) fibroblasts suggest that the encapsulated NPLs are capable of labelling the target cells enabling their visualization.Conclusion: As a result, we obtained water dispersible and temporally stable hydrophilic NPLs-loaded NCs that offer excellent, both one- and two-photon excited fluorescence preserving optical properties of the raw hydrophobic and colloidal NPLs. The biological responses upon eukaryotic cells indicate that the encapsulation process protects cells from the toxic influence of cadmium simultaneously preserving the unique multiphoton properties of the active cargo which opens a promising perspective for its application in multiphoton cancer bioimaging excited at the “optical transmission window” of biological tissues in near-infrared range.Keywords: semiconductor biomaterials, two-photon luminescence, nanodiagnostic agents, nonlinear optical properties, fibroblasts, cancer ovarian cells, laser diagnostics